Private values and public policy the ethics of decision making in government administration - Banks, Robert; First National Conference for Christians in the Public Service; Zadok Centre (Homebush West, NSW Lancer, 1983)
Includes bibliographical references.
Papers prepared for and given at the First National Conference for Christians in the Public Service; sponsored by the Zadok Centre, May 1983, Canberra.
Keywords: Government decision making -- ethics